The analysis of the deformation state of the double-wave guardrail mounted on bridges and viaducts of the motor roads in Lithuania and Ukraine - Prentkovskis, Olegas; Tretjakovas, Jurijus; Švedas, Audrius; Bieliatynskyi, Andrii; Daniunas, Alfonsas; Krayushkina, Kateryna (Journal of Civil Engineering and Management, 2012)
Traffic safety mainly depends on vehicles, pedestrians and road infrastructure. On highways, the heaviest traffic accidents are associated with crossing of the dividing strips by a vehicle and its collision with side obstacles on the junction or road bridge exit. These accidents often occur, when vehicles, running at a high speed, collide with obstacles, which may cause human injuries. In such cases, the probability of fatalities or heavy injuries to people in a traffic accident is very high. Road traffic infrastructure plays an important part in ensuring traffic safety on urban roads and highways. It includes guardrails, speed bumps, pedestrian safety islands, traffic regulation systems, road information infrastructure, etc. Guardrail (known as civil engineering element and traffic safety element) installation may help to reduce the number of human injuries and fatalities caused by traffic accidents. Guardrails of various types are installed on the roads of Lithuania and Ukraine. Guardrails, consisting of metal posts of the profile Σ and a protective beam of the profile W, i.e. ‘double-wave guardrails’, are among the most commonly used ones. The authors of this paper present the analysis of the deformation state of a double-wave guardrail (describing the strains and stresses of its elements).